Sexual behaviour and HIV infection in black-Africans in England: results from the Mayisha II survey of sexual attitudes and lifestyles. Issue 7 (11th October 2007) - Sadler, K E; McGarrigle, C A; Elam, G; Ssanyu-Sseruma, W; Davidson, O; Nichols, T; Mercey, D; Parry, J V; Fenton, K A
Abstract : Objectives: To estimate HIV prevalence and the distribution of high risk sexual behaviours, sexual health service use, and HIV testing among black Africans aged 16 years or over in England. To determine demographic, behavioural and service use factors associated with HIV prevalence. Methods: A cross-sectional community-based survey (Mayisha II) in London, Luton and the West Midlands. A short (24-item) anonymous self-completion questionnaire with linked voluntary anonymous oral fluid sampling, using an Orasure™ device for HIV testing. Results: A total of 1359 eligible black African men (51.9%) and women (48.1%) were recruited, of whom 74% (1006) provided a sufficient oral fluid sample for HIV testing. 42.9% of men and 50.9% of women reported ever having had an HIV test. Overall, 14.0% (141, 95% CI 11.9 to 16.3) of respondents tested HIV positive (13.1% of men and 15.0% of women); 9.2% (93) had undiagnosed HIV infection, while 4.8% (48) had a diagnosed HIV infection. HIV prevalence was significantly higher in men: born in East Africa; who had had a previous STI diagnosis; or who were recruited in bars and clubs; and in women: born in East or Southern Africa; aged 25 years and over; who had had two new sexual partners in the past 12 months; or who had had a previous STI diagnosis. Conclusions: Despite about half the sample having had an HIV test at some time in the past, 9.2% of respondents had an undiagnosed HIV infection. This study supports current policy efforts to further promote HIV testing and serostatus awareness.